Coatings to increase the corrosion behaviour of aluminium foam. (3rd June 2017) - Rossi, S.; Fedel, M.; Da Col, L.; Deflorian, F.; Petrolli, S.
Abstract : The aluminium foams present very interesting properties due to their low density. However, the presence of cells and the complex geometry are critical aspects considering the corrosion behaviour. A suitable method to increase the corrosion resistance is desirable. The cataphoretic deposited paint could be a useful way due to the possibility to obtain a protective and homogenous paint layer also with complex geometry. Other solution could be the application of an enamel layer, which shows high protection properties together with a good resistance at high temperature. The aim of this paper is the evaluation of the protection performance of these kinds of coatings. The corrosion behaviour of coated samples is evaluated by acetic acid salt spray exposure test and by electrochemical measurements. Both layers, organic coating and enamel, show a high increase of corrosion behaviour in comparison of uncoated aluminium foam.